Mechanochemical synthesis of nanohydroxyapatite bioceramics - Adzila, S.; Sopyan, I.; Yong, T.C.; Ramesh, Singh; Wong, Yew Hoong; Purbolaksono, J.; Hamdi, M. (NISCAIR, 2013)
Nanosized hydroxyapatite powder has been synthesized by the mechanochemical method using a dry mixture of calcium hydroxide and diammonium hydrogen phosphate. The effect of mechanochemical process on powder properties has been investigated. Three rotation speeds of 170 rpm, 270 rpm and 370 rpm have been employed with 15 hours milling time. Characterization of the nanopowders has been accomplished by Fourier transform infra red, X-ray diffraction and transmission electron microscopy analyses. The samples have been prepared and sintered in air at varying temperatures ranging from 1050–1350 °C. Results show that increase in rotation speed (370 rpm) increases the crystallite size (9–21 nm). Agglomerate formation with irregular shapes is found in the samples prepared at 270 and 370 rpm. The sintering process influences the stability of powder by yielding TCP phase at all the sintering temperatures. At 370 rpm, the sample sintered at 1250 °C shows the maximum relative density of 95.3% as well as hardness of 5.3 GPa.